Evaluation of exopolysaccharides producing lactic cultures for set and stirred fermented milk products - Behare, Pradip Vishnu (Indian Journal of Dairy Science, 2017)
Present investigation aims at technological screening of exopolysaccharides producing lactic acid cultures for manufacture of set and stirred fermented milk products. Twenty four Streptococcus and Lactobacillus cultures previously isolated from dairy sources were evaluated for their technological properties. Capsule formation and ropiness development by isolates varied within the species. The cultures designated as Kar1, Ram12, Ndri1 and Bha5 were highly ropy and produced more than 200 mg/L of exopolysaccharides in deproteinized whey. The remaining cultures found less to medium ropy. Viscosity of curd made by EPS cultures was higher than the non-EPS cultures. Firmness values of curd made by non-EPS cultures and capsular cultures were higher than the ropy cultures. Adhesiveness and stickiness values of skim milk fermented curd were increased for medium to highly ropy cultures. Based on technological properties capsular and medium ropy culture Kri4 and Ama6 found suitable for manufacture of dahi. The combination of capsular culture HH9 and Ama6 was better for yoghurt while highly ropy culture Ram12 for the preparation lassi. In conclusion, capsular and less to medium EPS producing lactic cultures may be used for manufacture of set product like dahi and yoghurt, while highly ropy cultures for preparation of stirred products.Â Â Â